ADVANCES IN COMPUTED TOMOGRAPHY IMAGING FOR CROHN’S DISEASE: A COMPREHENSIVE REVIEW - Yasser Ahmad Alahmad1,Maher Mohammed Abdulrahman Alotaibi2 Saeed Mesfer Bin Muidh Al Mutlaq3,Saud Fohaid Alqahtani4Bandar Mohammad Alajmi5,Rashed Saad Alqahtani6, Mohammad Awadh Alharbi7, Ayman Abdullah Almussad8 (Chelonian Research Foundation, 2022)
Crohn's disease (CD) is a chronic inflammatory disorder of the gastrointestinal tract characterized by transmural inflammation, strictures, and fistulas. Computed Tomography (CT) imaging has emerged as a cornerstone in the diagnosis, assessment of disease activity, and detection of complications in CD patients. This detailed review aims to comprehensively analyze recent advancements in CT imaging techniques, their clinical utility, limitations, and future directions in the management of Crohn's disease. We delve into various CT imaging modalities, including multi-detector CT (MDCT), CT enterography (CTE), and CT enteroclysis (CTEc), exploring their respective strengths, challenges, and clinical applications. Additionally, we discuss emerging trends such as radiation dose reduction strategies, quantitative imaging biomarkers, and the integration of artificial intelligence (AI) to enhance CD evaluation using CT imaging. By synthesizing current evidence and addressing key research gaps, this review provides valuable insights into optimizing CT imaging protocols, improving diagnostic accuracy, and guiding therapeutic decision-making in Crohn's disease. Keywords: Crohn's disease, Computed Tomography, CT enterography, CT enteroclysis, Imaging, Diagnosis, Disease monitoring.